Practical western irrigation - Hester, Mark V. (My University, 1894)
Introduction: As the eastern part of the United States is rapidly becoming more thickly populated, every nook and corner of ground is being brought into use. Better means of growing and cultivating crops are being devised all the time, rents have necessarily become higher and higher, and yet the supply is not efficient. In order to solve the problem of what to do next, the ever-progressive American people have steadily been pushing westward since the early Colonial days. It was in the ‘50’s that the tide of immigration had reached the borders of Kansas. Her delightful climate and fertile soil were evidently suited to agriculture, and so it has always proud to be. For the past thirty years, eastern Kansas has furnished as profitable farming lands and as happy homes as can be found in the United States. Again the supply is not sufficient. Land is too high-priced and too much rent is required. And again the tide moves on. Western Kansas, the Indian Territory, Texas, Colorado, and the other western states are to be used for agricultural purposes. But here very serious obstacles are encountered. The soil is as good as elsewhere, the air as pure, and the climate as delightful; but the soil and climate are different from farther east. Consequently other crops must be raised, men must learn how to raise them, and most of all there is not sufficient moisture at the time when most needed.
Citation: Hester, Mark V. Practical western irrigation. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Agriculture; Irrigation; Water; Crops; Kansas; Theses; Manuscripts (documents)